New concepts to support working parents in the car - Eardley, Rachel; Sellen, Abigail (Hewlett-Packard Labs Technical Report, 2004)
Working parents are an interesting segment of the population because they have heavy demands in both home and work spheres. In an initial, in-depth study, we discovered many different strategies that working parents employ to help them cope with work and family demands whether they are at work, at home or mobile. Following on from this first study, the validity and extent of car-related stresses for a larger sample of working parents was confirmed in a follow-up questionnaire involving 715 people in both the US and the UK. Here, we found many of the most severe everyday problems for working parents were related either specifically to being in the car, or were more general problems exacerbated by being mobile. On the basis of this finding, we conducted a follow-up workshop with six working parents to discuss car-related issues in more detail. The result is this catalogue of design ideas showing some of the initial concepts we have developed to help working parents cope with these and other stresses and strains of everyday life.